Muhammad Hasbi Siddiqi’ View on Sunnah | فكرة الأستاذ الدكتور محمّد حسبي الصّديقي عن السنّة النبوية - Laila Sabrina (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2016)
Muhammad hasbi as shiddieqie is one of indonesian moslem thinkers. He has manyworks in any diciplines of islamic studies such as fiqh, ushulul fiqh, tafsir and hadith. Inhadith, he has some difference ideas from other muhadithin. He distinguishes sunnahfrom hadith. According to him, hadith is an event leaning to the Prophet Muhammadalthough this event happened once in his life. Sunnah is mutawatir traditions andactivities which are done by Prophet Muhammad.